Fused λ5-Phosphinines: Design, Syntheses, and Properties - Hayashi, Minoru; Fujimoto, Shion; Ohta, Hidetoshi (Synlett, 2022)
Synthesis of several heterocycle-fused λ5-phosphinines through intramolecular cyclization is described. The incorporation of a heteroatom affected their photophysical properties through perturbation of the LUMO level, which is in good contrast to the HOMO-based tuning by the C-4 substituent. The C-3-substituent-based property tuning provides a new guide to designing phosphinine-based fluorophores.
Keywords: phosphinine; heteroaromatics; fluorescence; cyclization; coupling